Multiple sclerosis as an under-recognized cause of acute vertigo: clinical and pathophysiologic insights - Evangelos Anagnostou; Maria Kouvli (Frontiers in Neurology, 2026)
Multiple sclerosis (MS) is an autoimmune disorder that frequently presents with acute neurological symptoms during relapsing–remitting phases. While motor, sensory, and visual deficits are widely recognized manifestations of relapses, vestibular symptoms such as acute vertigo, dizziness, and imbalance are comparatively under-recognized and often pose diagnostic challenges. This review synthesizes foundational and recent evidence regarding MS-related acute vestibular syndrome and its central pathophysiologic mechanisms. Infratentorial demyelinating plaques, most frequently localized within the pons and the middle cerebellar peduncles, disrupt large fiber systems and give rise to distinct central oculomotor signs. We highlight highly characteristic ocular motor features—including internuclear ophthalmoplegia, wall-eyed bilateral INO, and acquired pendular nystagmus—that serve as crucial topodiagnostic clues. Furthermore, we address clinical mimics, distinguishing central positional nystagmus and vertigo from benign paroxysmal positional vertigo, the latter being highly prevalent and treatable via bedside maneuvers in MS populations. Crucially, this paper examines the limitations of bedside tools like the HINTS exam, which identify central pathology but fail to differentiate ischemic stroke from acute demyelination. In the emergency setting, integrating advanced neuroimaging—such as perfusion MRI, the central vein sign, and paramagnetic rim lesions—with detailed ocular motor evaluation is vital. Lastly, we explore atypical fascicular lesions mimicking peripheral vestibulopathy and hypothesize how delayed, desynchronized axonal conduction in MS may impair the precise timing of covert saccades required for vestibular recovery, warranting future cohort investigations.